2009
DOI: 10.2310/6670.2009.00027
|View full text |Cite
|
Sign up to set email alerts
|

May-Thurner Syndrome: Case Report and Review of the Literature Involving Modern Endovascular Therapy

Abstract: May-Thurner syndrome is a rare clinical entity involving venous obstruction of the left lower extremity. Obstruction occurs secondary to compression of the left common iliac vein between the right common iliac artery and the underlying vertebral body. Current management largely involves endovascular therapy. A review was conducted of six studies containing at least five patients with May-Thurner syndrome treated by endovascular therapy. We compiled data on 113 patients, analyzing patient demographics, treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 36 publications
3
111
1
1
Order By: Relevance
“…Interestingly, there is a left-sided predominance of proximal thrombosis during pregnancy that is thought to be due to an acquired compression of the left common iliac vein by the presence of the fetus (67). Similarly, individuals with May-Thurner syndrome suffer from compression of left common iliac vein that increases the risk of DVT (68).…”
Section: Reduced Blood Flow and Stasismentioning
confidence: 99%
“…Interestingly, there is a left-sided predominance of proximal thrombosis during pregnancy that is thought to be due to an acquired compression of the left common iliac vein by the presence of the fetus (67). Similarly, individuals with May-Thurner syndrome suffer from compression of left common iliac vein that increases the risk of DVT (68).…”
Section: Reduced Blood Flow and Stasismentioning
confidence: 99%
“…51 Other causes of IVC thrombosis include May-Thurner syndrome, which causes ilio-femoral thrombosis because of an intraluminal web or stenosis of the left common iliac vein, likely due to the direct mechanical impingement of the right common iliac artery on the left common iliac vein. 52 Although Budd-Chiari syndrome (primary hepatic vein thrombosis) is a hypertensive syndrome of the hepatic veins, it has features in common with IVC thrombosis owing to altered haemodynamics of the hepatic veins, IVC and portal vein. 53 …”
Section: Acquired Ivc Thrombosismentioning
confidence: 99%
“…5,16 In the case of a DVT associated with MTS, systemic anticoagulation alone is not adequate, as it fails to address the underlying anatomical compression. 24,25 It is suggested that the anatomical defect should be repaired with the use of stents and balloon venoplasty. 11 Patients with a high clot burden should also undergo inferior vena cava filter placement.…”
Section: Managementmentioning
confidence: 99%